E-publishing and digital libraries : legal and organizational issues - Synodinou, Tatiana-Helene.; Kapidakis, Sarantos; Iglezakis, Ioannis, 1965- (Hershey, PA : Information Science Reference, 2011)
'In this book, a comprehensive review of various legal issues concerning digital libraries is presented'--Provided by publisher.
Includes bibliographical references (p. 482=512) and index.
Keywords: Digital libraries; Libraries and electronic publishing; Copyright -- Electronic information resources; Digital preservation